Polypyrimidine tract binding protein knockdown reverses depression-like behaviors and cognition impairment in mice with lesioned cholinergic neurons - Zhou, Yiying; Zhang, Ke; Wang, Fangmin; Chen, Jiali; Chen, Shanshan; Wu, Manqing; Lai, Miaojun; Zhang, Yisheng; Zhou, Wenhua (Frontiers in Aging Neuroscience, 2023)
Background and objectives Depression is a common comorbidity of dementia and may be a risk factor for dementia. Accumulating evidence has suggested that the cholinergic system plays a central role in dementia and depression, and the loss of cholinergic neurons is associated with memory decline in aging and Alzheimer’s patients. A specific loss of cholinergic neurons in the horizontal limb of the diagonal band of Broca (HDB) is correlated with depression and dysfunction of cognition in mice. In this study, we examined the potential regenerative mechanisms of knockdown the RNA-binding protein polypyrimidine tract binding protein (PTB) in reversing depression-like behaviors and cognition impairment in mice with lesioned cholinergic neurons. Methods We lesioned cholinergic neurons in mice induced by injection of 192 IgG-saporin into HDB; then, we injected either antisense oligonucleotides or adeno-associated virus-shRNA (GFAP promoter) into the injured area of HDB to deplete PTB followed by a broad range of methodologies including behavioral examinations, Western blot, RT-qPCR and immunofluorescence. Results We found that the conversion of astrocytes to newborn neurons by using antisense oligonucleotides on PTB in vitro, and depletion of PTB using either antisense oligonucleotides or adeno-associated virus-shRNA into the injured area of HDB could specifically transform astrocytes into cholinergic neurons. Meanwhile, knockdown of PTB by both approaches could relieve the depression-like behaviors shown by sucrose preference, forced swimming or tail-suspension tests, and alleviate cognitive impairment such as fear conditioning and novel object recognition in mice with lesioned cholinergic neurons. Conclusion These findings suggest that supplementing cholinergic neurons after PTB knockdown may be a promising therapeutic strategy to revert depression-like behaviors and cognitive impairment.